Mehmed pasha Sokollu - ethnic, national and cultural fixture problems - Mikołajczak, Marcin (Balcanica Posnaniensia. Acta et studia, 2009)
The article analyzes the issue of the ethnic, national, and cultural affiliation of Mehmed Pasha Sokollu (c. 1505–1579), one of the most outstanding grand viziers of the sixteenth-century Ottoman Empire. The background of the study is the complex political and religious situation of the Balkans, which at that time constituted a space of intense intercultural contact and identity conflicts. The aim of the research is to present various interpretations of Sokollu’s origin found in Serbian, Croatian, Bosnian, Turkish, and European historiography, and to demonstrate how this figure was used in shaping national historical narratives. The analysis is based on studies by nineteenth- and twentieth-century historians, as well as on Turkish, Serbian, Croatian, and Bosnian sources, including diplomatic reports and contemporary chronicles. The author employs a comparative method of source and interpretation analysis, focusing on the evolution of Mehmed Pasha’s image in relation to changing ideological and national needs. The findings show that the figure of Sokollu became a symbolic focal point in the dispute over the cultural heritage of the Balkans. Depending on the narrative, he was regarded as a Serb, Croat, Bosnian, or even a Turk. At the same time, his political activity - such as the renewal of the Patriarchate of Peć and the development of infrastructure—proves that he functioned beyond ethnic and religious boundaries. The article concludes that Mehmed Pasha Sokollu represents a historical example of a statesman who balanced loyalty to the Ottoman Empire with a remembrance of his Balkan roots, becoming a figure that unites rather than divides diverse cultural traditions.